Host and geographically related genetic variation in species of Cloacina (Nematoda: Strongyloidea) from western and eastern grey kangaroos, Macropus fuliginosus and M. giganteus (Marsupialia: Macropodidae) - Shane Gerald Middleton; Anson Koehler; Ian Beveridge (Parasitology)
Specimens of Cloacina artemis, C. expansa, C. hera, C. hermes, C. hestia, C. magnipapillata, C. obtusa and C. selene, which occur in both of the closely related species of grey kangaroos, Macropus fuliginosus and M. giganteus, were found to differ genetically based on sequence data derived from the internal transcribed spacers (ITS-1, ITS-2) of ribosomal DNA. The extent of differences varied from a single base pair in C. expansa, to 32 in C. hestia. In the case of C. hera, C. hestia and C. magnipapillata, separate genotypes were found in M. fuliginosus and M. giganteus. With C. artemis, C. expansa, C. obtusa and C. selene, nematode genotypes did not correspond with host distributions. In C. hermes, two genotypes were detected but they were not related phylogenetically. The data provide evidence suggestive of genetic differentiation in most of the nematode species potentially associated with host speciation, but with differing degrees of genetic differentiation and different associations with the two host species possibly related to changes in the geographical distribution of the hosts over time.